Repositioning of Cefuroxime as novel selective inhibitor of the thyroid hormone activating enzyme type 2 deiodinase. (March 2023) - Sagliocchi, Serena; Murolo, Melania; Cicatiello, Annunziata Gaetana; Miro, Caterina; Nappi, Annarita; Di Cicco, Emery; Torabinejad, Sepehr; La Civita, Evelina; Romano, Veronica; Terracciano, Daniela; Stornaiuolo, Mariano; Dentice, Monica
Abstract: The iodothyronine deiodinases constitute a family of three selenoenzymes regulating the intracellular metabolism of Thyroid Hormones (THs, T4 and T3) and impacting on several physiological processes, including energy metabolism, development and cell differentiation. The type 1, 2 and 3 deiodinases (D1, D2, and D3), are sensitive, rate-limiting components within the TH axis, and rapidly control TH action in physiological conditions or disease. Notably, several human pathologies are characterized by deiodinases deregulation ( e.g., inflammation, osteoporosis, metabolic syndrome, muscle wasting and cancer). Consequently, these enzymes are golden targets for the identification and development of pharmacological compounds endowed with modulatory activities. However, until now, the portfolio of inhibitors for deiodinases is limited and the few active compounds lack selectivity. Here, we describe the cephalosporin Cefuroxime as a novel D2 specific inhibitor. In both in vivo and in vitro settings, Cefuroxime acts as a selective inhibitor of D2 activity, without altering the enzymatic activity of D1 and D3. By inhibiting TH activation in target tissues, Cefuroxime alters the sensitivity of the hypothalamus-pituitary axis and interferes with the central regulation of THs levels, and is thus eligible as a potential new regulator of hyperthyroid pathologies, which affect thousands of patients worldwide. Graphical Abstract: ga1 Highlights: Cefuroxime inhibits the activity of D2, the thyroid hormone activating enzyme. By inhibiting D2, Cefuroxime interferes with TH activation in muscle cells. In vivo administration of Cefuroxime blocks TH activation in peripheral tissues. Cefuroxime treatment of hypothyroid mice reduces the sensibility of the HPT axis.